INSTAGRAM IN TEACHING ENGLISH FOR SPECIFIC ACADEMIC PURPOSES - Eva Maierová (Novìtnâ Osvìta)
The purpose of the study is to explore the potential of integrating Instagram in university-level English for Specific Academic Purposes (ESAP) courses, focusing on Business English for Advanced Students. Using a mixed-methods approach, it combines qualitative data from observing the completion of Instagram-based assignments and subsequent semi-structured group interviews with quantitative data from a five-point Likert scale questionnaire distributed to the students who participated in the study. The research sample consisted of twenty-six undergraduate students from the Faculty of Commerce at the University of Economics in Bratislava, Slovakia, who completed four Instagram-based tasks related to communication, international marketing, promoting Slovakia, and success, which were linked to topics covered in the course during the winter semester of the academic year 2020/2021. The findings show that Instagram can be used effectively in ESAP courses mainly due to its popularity, visual appeal of posts, and, most importantly, as a platform that serves as a powerful marketing tool. The results indicate that the implementation of Instagram activities was positively perceived by most students, with high levels of agreement regarding the relevance, engagement, and creativity of the tasks. The study highlights the potential benefits of using Instagram in ESAP, providing insights into effective language learning through authentic, business-related tasks. Ultimately, integrating Instagram into ESAP can enable students to develop the language skills and competencies needed in real business contexts.